Intermediate Accounting–A Functional Approach (Book). - Zeff, Stephen A.; Donley, Hervey E. (The Accounting Review, 1962)
Reviews the book "Intermediate Accounting–A Functional Approach," by C.A. Moyer and R.K. Mautz.